Can moral reminders curb corruption? Evidence from an online classroom experiment - Corinna Claus; Ekkehard A. Köhler; Tim Krieger (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2022)
Using an incentivized online classroom experiment, we assess the effectiveness of deontological vs. consequentialist moral reminders. Participants were told that they are the responsible public servant for acquiring a Covid-19 vaccine, providing them with the opportunity to generate some extra private income by accepting a bribe. Our findings indicate that a deontological moral reminder ("corruption is immoral") leads to a significant reduction in accepting bribes. A consequentialist moral reminder, pointing out that bribes are costly to taxpayers, shows no significant effect. Furthermore, we do not find any empirical support that male participants are more corrupt in comparison to female participants. Students majoring in economics or business/management show more corrupt behavior than students studying to become economics school teachers, but the difference is not statistically significant. A person's disposition towards risk appears to have a strong dissuading effects. Our experiment was conducted before and after the unexpected announcement by pharmaceutical companies BioNTech and Pfizer on November 9th, 2020, that they will be able to provide an effective Covid-19 vaccine. This announcement does not correlate with a changed level of bribe-taking.
Keywords: A20; C91; D73; H12; I20; 330; Moral Reminder; Ethics; Corruption; Dishonesty; Economics Students; Experiment; Covid-19